2015
DOI: 10.1186/s12889-015-1873-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultural activity participation and associations with self-perceived health, life-satisfaction and mental health: the Young HUNT Study, Norway

Abstract: BackgroundLeisure time activities and culture participation may have health effects and be important in pulic health promotion. More knowledge on how cultural activity participation may influence self-perceived health, life-satisfaction, self-esteem and mental health is needed.MethodsThis article use data from the general population-based Norwegian HUNT Study, using the cross-sectional Young-HUNT3 (2006–08) Survey including 8200 adolescents. Data on cultural activity participation, self-perceived health, life-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
4
24
1
2
Order By: Relevance
“…Regarding cultural aspects, although the data indicated association with significance only for religious practice and attendance at museums, a Norwegian study of 8,085 adolescents aged 13 to 19 indicated that participation in other cultural activities may be positively associated with self-perception of health, satisfaction with life and self-esteem in adolescents 24 . It is worth considering that although there is little research dedicated to understand the cultural aspects in adolescent health, it is necessary to expand this analysis, since it may constitute an important axis in the discussion of opportunities and self-concept in this life cycle.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding cultural aspects, although the data indicated association with significance only for religious practice and attendance at museums, a Norwegian study of 8,085 adolescents aged 13 to 19 indicated that participation in other cultural activities may be positively associated with self-perception of health, satisfaction with life and self-esteem in adolescents 24 . It is worth considering that although there is little research dedicated to understand the cultural aspects in adolescent health, it is necessary to expand this analysis, since it may constitute an important axis in the discussion of opportunities and self-concept in this life cycle.…”
Section: Discussionmentioning
confidence: 90%
“…Selv om en i en tverrsnitts studie ikke kan uttale seg om årsak og virkning kan resultatene likevel støtte opp under resultatene som rapporteres fra studien til (Hansen et al, 2015), hvor de undersøkte sammenheng mellom deltakelse i kulturell aktivitet og angst og depresjon blant barn og unge i alderen 13-19 år, hvor det ikke ble rapportert noen signifikant positiv sammenheng mellom deltakelse i kulturell aktivitet og lave skåre på angst og depresjon. I studien til Hansen et al (2015) ble kulturopplevelser som kinobesøk, organisert trening, og deltakelse i utøvende kulturelle aktiviteter definert som kulturell aktivitet. Det at Hansen og kollegaer har definert organisert trening (idrett) inn i kulturell aktivitet, kan gjøre det utfordrende å sammenligne resultatene når vi i vår studie skiller idrettsdeltakelse fra kulturell deltakelse.…”
Section: Diskusjonunclassified
“…In einer Studie konnte bei älteren Personen ( > 75 Jahre) gezeigt werden, dass regelmäßige Freizeitaktivitäten, darunter insbesondere das Spielen eines Instrumentes, mit einem geringeren Risiko für Demenzerkrankungen assoziiert waren [15]. Auch bei Jugendlichen wurden positive Zusammenhänge zwischen der Teilnahme an kulturellen Aktivitäten und Gesundheit, Lebenszufriedenheit sowie Selbstachtung beobachtet [16].…”
Section: Wie Ist Die Datenlage?unclassified